Peran Customer Experience dan Customer Participation terhadap Customer Loyalty melalui Value Co-Creation sebagai Variabel Intervening pada Pengguna GrabFood di Semarang - Wahyu Rizki Prayitno; Asyhari (ARZUSIN, 2026)
Increasing competition in the online food delivery industry requires GrabFood to strengthen customer loyalty. However, high levels of customer experience and customer participation do not necessarily lead directly to customer loyalty; therefore, the mechanism of value co-creation needs to be examined as a link between these constructs. This study aimed to analyze the effects of customer experience and customer participation on customer loyalty, both directly and through value co-creation as an intervening variable among GrabFood users in Semarang City. The study employed a quantitative approach involving 200 GrabFood users selected through purposive sampling. Primary data were collected using a questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that customer experience and customer participation had positive and significant effects on value co-creation. However, neither variable had a significant direct effect on customer loyalty. Conversely, value co-creation had a positive and significant effect on customer loyalty and fully mediated the effects of customer experience and customer participation on customer loyalty. This study concludes that loyalty among GrabFood users is formed through a value co-creation mechanism rather than solely through customer experience or direct customer participation. These findings underscore the importance of strategies that facilitate customers’ active involvement in value creation to strengthen loyalty to GrabFood services.